CD8+ T cells in OA knee joints are differentiated into subsets depending on OA stage and compartment - Platzer, Hadrian; Trauth, Richard; Nees, Timo A.; Tripel, Elena; Gantz, Simone; Schiltenwolf, Marcus; Moradi, Babak; Rosshirt, Nils (Journal of Clinical Medicine, 2022)
Osteoarthritis (OA) is no longer considered a purely degenerative disease. OA is defined as a disease of the entire joint, in which inflammation occurs in various joint tissues. The overall aim of this study was to analyze the presence and polarization of CD8+ T cell subsets in OA knee joints, in relation to the OA stage and compartment (synovial fluid (SF), synovial membrane (SM,) peripheral blood (PB)). A quantitative flow analysis of CD8+ T cell subsets to compare the SF, SM, PB, was performed in patients with different stages of OA (early, unicondylar and bicondylar OA). Samples of the SF, SM and PB were harvested from a total of 55 patients at the time of surgery. Early OA was confirmed by independent surgeons intraoperatively. Uni- and bicondylar OA was confirmed and graded by two plane radiographs. Samples were analyzed by flow cytometry for surface markers, and cytokines by intracellular staining (ICS). CD8+ T cells were shown to be differentiated into pro-inflammatory IFN-γ producing Tc1 and IL-17A producing Tc17, as well as anti-inflammatory IL-4 producing Tc2. All CD8+ T cell subsets (Tc1, Tc17, and Tc2) were detected in both the SM and SF. The percentage of CD8+ T cell subsets of the total CD8+ T cell population was dependent on the OA stage and compartment. Compared with the peripheral blood (PB), the proportion of CD8+IFN-γ+ Tc1 and CD8+IL-17A+ Tc17 was significantly increased in OA SF. This was confirmed in our data for both early OA and end-stage OA. In the SM samples of end-stage OA patients, the proportion of CD8+IL-17A+ Tc17 was significantly increased compared to the PB. Comparing SF and SM samples of end-stage OA patients, the proportion of CD8+IFN-γ+ Tc1 was significantly increased in SF, whereas there were no differences concerning CD8+IL-4+ Tc2 and CD8+IL-17A+ Tc17. End-stage OA samples showed a significant increase of CD8+IL-4+ Tc2 in the SM for both unicondylar and bicondylar OA compared to early OA. CD8+ T cells infiltrating the SM and SF in OA knees are differentiated into IFN-γ-, IL-17A-, and IL-4-producing CD8+ T cell subsets (Tc1, Tc17, Tc2). This differentiation depends on the OA stage and OA compartment. Further investigation of CD8+ T cell subsets and their interaction with other inflammatory cells such as CD4+ T cells and macrophages may help to identify novel therapeutic anti-inflammatory strategies for containing OA progression.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 30.06.2022